Problems of civil rights protection - Berdiugin S. R., Evdakimov N. S. (Interactive science, 2018)
the article points out the strengthening of positions in the conditions of global integration of space of the Russian Federation in the world arena. especial attention is paid to the problems of protection and realization of civil rights and fulfillment of civic duties of proper character. Also, the main problems of realization and protection of civil rights are analyzed in the article.
Keywords: злоупотребление правом; гражданско-правовая ответственность; гражданские права; способы осуществления; самозащита гражданских прав; ways of implementation; abuse of law; civil rights; civil liability; self-defense of civil rights